Health Spending in Uganda Implications on the National Minimum Health Care Package - Lukwago, Daniel (ACODE, 2016)
This policy brief is part of Public Expenditure Governance (PEG) study of the health sector in Uganda. The overall objective of the research was to examine the links between public spending, governance, and outcomes in the health sector and the specific objectives of the study were to identify the actors and their roles in decision making regarding budget allocations and service delivery, develop indicators for assessing expenditure governance in the health sector, Identify and assesse the effects of budget allocation decisions on health sector performance and finally to identify and assess the efficiency of accountability mechanisms, including community participation, sanctions and rewards. Funding remains the single most important constraint facing the health sector in Uganda. Although the Government budget allocation to the health sector has increased from UGX 660 billion in 2010/11 to UGX 1,271 billion in 2015/16, the sector share of the total national budget averaged 7.8% during the same period which is 2 percentage points short of the HSSIP target of 9.8%.